2018
DOI: 10.1097/sap.0000000000001444
|View full text |Cite
|
Sign up to set email alerts
|

Functional Results of a Modified Extracorporeal Septoplasty With Open Access

Abstract: Based on the results obtained from our work, we can declare that open access is a functionally valid procedure. At 6 months after surgery, the 2 accesses have a comparable functional efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Fifty-nine articles were selected for a full review with 17 meeting the inclusion criteria. 6-10,12-22 Of the 17 studies selected, 10 studies recorded subjective functional outcome data, four studies provided objective functional outcome data, three studies provided subjective aesthetic outcome data, and six studies provided objective aesthetic outcome data—Table 1. Three studies reported the complication rate with no functional and/or aesthetic outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-nine articles were selected for a full review with 17 meeting the inclusion criteria. 6-10,12-22 Of the 17 studies selected, 10 studies recorded subjective functional outcome data, four studies provided objective functional outcome data, three studies provided subjective aesthetic outcome data, and six studies provided objective aesthetic outcome data—Table 1. Three studies reported the complication rate with no functional and/or aesthetic outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…An I-shaped deformity is defined by the tip deviation angle, which is the angle formed from a vertical reference line from the center of the radix down to the cupid’s bow, and a line drawn from the center of the radix to the middle of the nasal tip. 22 The lack of an I-shaped deviation (ie, a perfectly straight nose) results in a measured angle of 0°. In contrast, a C-shaped deviation is defined as the angle created by drawing an oblique line from the nasion to the most extreme point of convexity and then to the nasal tip.…”
Section: Resultsmentioning
confidence: 99%
“…18 There are many current studies that demonstrate the ESR outcomes in long-term success with decrease from severe preoperative to lighter postoperative symptoms. About the influence of ESR technique on the nasal obstruction, Marangi et al 19 compared the NOSE scores and acoustic rhinomanometry after ES technique and ESR technique with 50 patients. The authors reported that rhinomanometric scores in the ES group were higher than in the ESR group at 3 months postoperatively and this difference disappeared at 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores meant serious nasal obstruction. According to the NOSE Scale results, the patients were categorized as mild (1-5), moderate (6)(7)(8)(9)(10), severe (11)(12)(13)(14)(15), or extreme (16)(17)(18)(19)(20).…”
Section: Outcome Datamentioning
confidence: 99%
“…La desviación del tabique nasal es una de las principales causas de los trastornos obstructivos nasales (2). Una deformidad de la pirámide por su parte, aunque no produzca obstrucción, puede acarrear gran molestia para el paciente, alterando su autoconfianza y funcionamiento mental y psicosocial (3).…”
Section: Introduccionunclassified